Axenic in vitro cultivation and genome diploidization of the moss Vesicularia montagnei for horticulture utilization - Hu, Yong; Li, Qing; Chen, Zexi; Xu, Zhanwu; Li, Hongyu; Wen, Congfa; Duan, Liu; Yang, Hong; Liu, Li (Frontiers in Plant Science, 2023)
Mosses are widely used in the establishment of greenery as horticultural plants. However, little research has been conducted to select a proper specie or improve their performance for this application. Our study examined a robust moss, Vesicularia montagnei (V. montagnei), which is widely distributed in temperate, subtropical, and tropical Asia with different environmental conditions. For a sustainable way of obtaining V. montagnei plants, our study established an axenic cultivation system. Increasement of rhizoid length and density was accomplished with artificially induced diploidization of V. montagnei, which may improve the ability to attach to the supporting objects in the application practices. Transcriptomic analysis revealed that the elevation of expression levels of several genes responsible for jasmonic acid (JA) biosynthesis, which is consistent with the increased JA content in the diploid lines. Our study not only established the method for cultivating Vesicularia montagnei, but also provided helpful information for better understanding the biosynthesis and functions of JA in the early landed plants.